In Silico Prediction of Heliannuol A, B, C, D, and E Compounds on Estrogen Receptor β Agonists - Roihatul Mutiah; Alif Firman Firdausy; Yen Yen Ari Indrawijaya; Hibbatullah Hibbbatullah (Indonesian Society for Cancer Chemoprevention, 2021)
Heliannuols has a benzoxepine ring that produces anticancer activity by the inhibition mechanism of phosphoinositide 3 kinases (PI3K). Heliannuols are a compound that can be found in the leaves of sunflower (Helianthus annuus L.). The purpose of this study is to predict interactions, toxicity, physicochemical, and pharmacokinetics of Heliannuol A, B, C, D, and E based in silico as candidate anticancer drugs. Estrogen receptor beta (ERβ) is a new potential therapy for glioma with an antiproliferative effect. Ligands agonist ERβ have the potential activity to inhibit the proliferation of glioma cells and the discovery of this ligand has opened new therapy through the ERβ to prolong survival in cancer patients. Prediction of physicochemical properties based on Lipinski rules and penetrate in the blood-brain barrier. Receptor validation shows that 2I0G(A) has a smaller RMSD value than 2I0G(B), receptor validation is valid if the RMSD value less than 2. The result of molecular docking shows that Heliannuols comply with Lipinski rules and have low toxicity. Heliannuols also have a similar amino acid with Erteberel, but the rerank score of Erteberel still lower than Heliannuols.Keywords: Helianthus annuus, Heliannuols, estrogen receptor β (ERβ), in silico, toxicity.